2021
DOI: 10.35445/alishlah.v13i3.1457
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Trailer Film to Increase English Essay Writing

Abstract: Essay writing has a fairly complex level of difficulty. Moreover, the online and offline learning process in the era of technological progress has directed learning activities to be carried out through technological innovation. The purpose of this study was to determine the impact of film trailers on improving English essay writing skills for students at Bina Sarana Informatika University, Jakarta. The research method uses experiments with a one-group experimental design. Participants were taken using a purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Baharuddin and Mohamad (2020) suggested that while vocabulary improved through blog features, there was no significant progress in grammar. Conversely, Meinawati et al in 2023 in their studies reported positive developments in grammar among participants. Bal (2021) also noted learners' improved in writing skills, language practice, and grammar enhancement through blogs.…”
Section: Grammar and Mechanicsmentioning
confidence: 84%
See 2 more Smart Citations
“…Baharuddin and Mohamad (2020) suggested that while vocabulary improved through blog features, there was no significant progress in grammar. Conversely, Meinawati et al in 2023 in their studies reported positive developments in grammar among participants. Bal (2021) also noted learners' improved in writing skills, language practice, and grammar enhancement through blogs.…”
Section: Grammar and Mechanicsmentioning
confidence: 84%
“…The research consistently showed positive outcomes in the area of writing proficiency. Notable contributors to these findings include studies conducted by Ningsih et al, 2023;Meinawati et al, 2023;Siddique et al, 2023;Aljafen, 2023;Mohamed & Abdellatif , 2023;Yesuf et al, 2022;Al-Jarf, 2022;Alenezi, 2022;Han, 2022;Perumal, 2022;Alied et al, 2022;Yousefifard, 2021;Bal, 2021;Muslem et al, 2021;Rahayu, 2021;Restapaty, 2021;Sütçü, 2020;Dewi R et al, 2020;Albashir et al, 2020;Kazancı & Caner, 2020;Elsawi, 2020;Mashaeal & Altalhab, 2020;Baharuddin & Mohamad, 2020;Priya, 2020 andPham &Nguyen, 2020. The collective evidence from these studies consistently supports the positive impact of blog integration on students' writing skills (Ningsih et al, 2023;Meinawati et al, 2023;Siddique et al, 2023;Aljafen, 2023;Mohamed, 2022;Yesuf et al, 2022;Al-Jarf, 2022;Alenezi, 2022;Han, 2022;Perumal, 2022;Alied et al, 2022;Yousefifard, 2021;Bal, 2021;Muslem A et al, 2021;Rahayu, 2021;Restapaty, 2021;Sütçü, 2020;Dewi R et al, 2020;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, films are often used as a medium for developing story ideas in writing essays. innovation (Meinawati et al, 2021). Even films can be a project-based learning model to improve writing skills (Meinawati, 2020).…”
Section: Graph 5 Idea Help Students In Making Writing Scenariosmentioning
confidence: 99%
“…One way of bringing variety into the classroom is the use of films in teaching EFL. Films grab students' attention, present language in a more natural way found in textbooks and offer visual context aids that help students understand and improve their study skills (Ismaili, 2013;Ergenekon, 2016;Bonsignori, 2018; Euis Meinawati, Prapti Wigati Purwaningrum, Sufi Alawiyah, Herlin Widasiwi Setianingrum / The Effectiveness of YouTube as an E-Resource on Students' Writing Learning Meinawati, 2020;Meinawati et al, 2021). The selection of clips from films and TV series can also provide a choice of genres that you want to learn for writing activities (Bonsignori, 2018).…”
Section: Introductionmentioning
confidence: 99%